Agrarian archaeology in northwestern Iberia : local societies : the off-site record - Quirós Castillo, Juan Antonio, (Historical archaeologies series., 2023)
Devoted to the archaeological study of the societies and agrarian landscapes of Northwestern Iberia in the longue durée, this book brings together the results of some of the main projects carried out in recent decades from off-site records, providing a fresh perspective for the understanding of historical landscapes.